Pentecostal ecclesiology in the new adaptation era: - J. Gultom; D. Ming (Acta Theologica)
The Synod of the Gereja Bethel Indonesia/GBI (Bethel Church of Indonesia) is Indonesia’s largest Protestant and Pentecostal denomination, with over 7,000 local churches and nearly three million church members. It is, therefore, significant to discuss this church. Over the past three years, the COVID-19 pandemic has forced churches worldwide to adjust to the off-site system of worship and ministry. The pandemic also led to the speedy acceleration of digital technology. Consequently, it called for redefining and repositioning our ecclesiology and praxis. This article presents the theological position of GBI in a new era of adaptation as a result of the COVID-19 pandemic. This article uses a systematic approach, by briefly introducing the concepts of ecclesiology and fellowship, then developing these concepts further with concrete and relevant examples in the context of the GBI church.